City’s Authenticity: Examining Community Participation in Rebuilding Buraydah Historical Gates, Al-Qassim, Saudi Arabia - Rahmayati, Yenny; Alsaid, Renad (Institute for Advanced Science Social, and Sustainable Future, 2024)
The historical gates of Buraydah are an important heritage site in Al-Qassim, Saudi Arabia. The Gates were built between 1850 and 1901 to protect the city but were demolished later, leaving almost no records or plans behind. The Prince of Al-Qassim has taken on the project to rebuild the Gates to teach future generations about their culture and heritage. The participation of the community becomes essential in this case. This study examines the role of the local community in the rebuilding process by questioning the extent of community participation to ensure the city's authenticity and how to enhance its involvement in the process. To achieve this objective, the study employed a combination of qualitative and quantitative methods for primary data collecting through online surveys. It was supported by a literature study as supplementary data especially to trace the history of the Gates. The aim is to provide a complete picture of the Buraydah Gates, including its history, how they were built and demolished, and their significance to the community in the present times. This project is not like most other rebuilding projects we see today. It is not a case of looking at old plans and drawings and recreating them. It argues that community participation through scouring for rare photographs of the original gate and drawing plans based on the perception of the elderly recalling the design is the most effective approach to ensure the city’s authenticity. In addition, this project stands out because it is based on what the community remembers and feels about the gates. However, many aspects of this site are undocumented, and it is imperative to record and make notes of the progression in order to serve our future generations this study enriches that documentation.